Terminal assembly of sarcomeric filaments by intermolecular beta-sheet formation. - Pinotsis, N; Abrusci, P; Djinović-Carugo, K; Wilmanns, M (2009)
The contraction-relaxation cycle of muscle cells translates into large movements of several filament systems in sarcomeres, requiring special molecular mechanisms to maintain their structural integrity. Recent structural and functional data from three filaments harboring extensive arrays of immunoglobulin-like domains - titin, filamin and myomesin--have, for the first time, unraveled a common function of their terminal domains: assembly and anchoring of the respective filaments. In each case, the protein-protein interactions are mediated by antiparallel dimerization modules via intermolecular beta-sheets. These observations on terminal filament assembly indicate an attractive model for several other filament proteins that require structural characterization.